2014
DOI: 10.1080/03601234.2014.929481
|View full text |Cite
|
Sign up to set email alerts
|

Application of various methods to determine the lipophilicity parameters of the selected urea pesticides as predictors of their bioaccumulation

Abstract: Different lipophilicity procedures including a newly developed (based on Ościk's equation) was applied in order to compare various urea pesticides with herbicidal and also insecticidal activity, such as monolinuron, chlorotoluron, diuron, isoproturon, linuron, dimefuron, diflubenzuron, teflubenzuron and lufenuron. Lipophilicity parameters (RMWS and RMW0) of nine examined pesticides were determined on the chromatographic plates RP-8F254 with the use of methanol-water as a mobile phase. Similarity analysis enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…One of the most important physicochemical properties is lipophilicity. Estimations of n-octanol/water partition coefficient (logP ow ), which allows lipophilic character appraisals, are considerable in the field of agrochemical industry, environmental monitoring, and pharmacology (Dolowy et al, 2014;Skyner et al,2015). It is known that the presence of fluorine substituents in bioactive molecules increases lipophilicity.…”
Section: Lipophilic Character Analysismentioning
confidence: 99%
“…One of the most important physicochemical properties is lipophilicity. Estimations of n-octanol/water partition coefficient (logP ow ), which allows lipophilic character appraisals, are considerable in the field of agrochemical industry, environmental monitoring, and pharmacology (Dolowy et al, 2014;Skyner et al,2015). It is known that the presence of fluorine substituents in bioactive molecules increases lipophilicity.…”
Section: Lipophilic Character Analysismentioning
confidence: 99%
“…The results confirmed that a new procedure for determining the lipophilicity parameter (R MW0 ) by Oscik's equation could be a suitable tool for the prediction of pesticide bioaccumulation in living systems and may be used as an indicator in the design of new urea pesticides that will be safe for humans and the environment. [29] As will be evident in the following sections, by far most TLC analyses of pesticides are carried out on normal phase (NP) silica gel 60 F 254 plates with 100-250-um layer thickness (usually thicker for PLC) with ascending capillary action development in large volume chambers rather than the conditions used in the studies above. Ultra thin layer chromatography (UTLC) glass plates with a directly bound 10-um thick monolithic or nanostructured silica gel layer have also been used for separations of pesticides.…”
Section: Introductionmentioning
confidence: 99%